The CISO evolution : business knowledge for cybersecurity executives - Sharp, Matthew K.; Lambros, Kyriakos P. (Ascent Audio, 2022)
Learn to effectively deliver business aligned cybersecurity outcomes In The CISO Evolution: Business Knowledge for Cybersecurity Executives, information security experts Matthew K. Sharp and Kyriakos "Rock" Lambros deliver an insightful and practical resource to help cybersecurity professionals develop the skills they need to effectively communicate with senior management and boards. They assert business aligned cybersecurity is crucial and demonstrate how business acumen is being put into action to deliver meaningful business outcomes. The authors use illustrative stories to show professionals how to establish an executive presence and avoid the most common pitfalls experienced by technology experts when speaking and presenting to executives. The book will show you how to: - Inspire trust in senior business leaders by properly aligning and setting expectations around risk appetite and capital allocation - Properly characterize the indispensable role of cybersecurity in your company's overall strategic plan - Acquire the necessary funding and resources for your company's cybersecurity program and avoid the stress and anxiety that comes with underfunding.